(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
Mortadella was processed from second beef meat was prepared by adding soybean meal(whole fat, skimmed) at different rates of 11, 13, 15, 17, 19 and 21%. The change in the chemical composition (moisture, protein, fat, chloride Sodium, ash, acidity, pH, peroxide), as well as changes in sensory properties (taste, color, texture, odor, appearance), microbial properties (general census of aerobic bacteria, yeasts and molds, E. coli, salmonella). The results of the chemical analysis showed that the moisture of the mardadella increases with the percentage of added soy meal to become outside the standard in the proportion of soya 21%. As for the ash, the ash content is high with the percentage of added soy flour, but it remains below the 3.2% specified in the specification. For the protein, all the samples with the control within the standard (12% minimum) with the high percentage of protein by adding soy flour, and for the salt, its percentage in all samples is in accordance with the specification ( 2% maximum), as for Peroxide values ​​showed a decrease in the proportion of soy flour. Sensory tests showed that all sensory properties improved by adding soybean meal in all mixtures, except for mixtures, where the proportion of soy meal 21%. The microbial tests showed that there were no pathogens, especially Salmonella and E. coli, and showed that the total population of air bacteria, yeasts and breakfast was within the limits of the Syrian standard. There was a decrease in the general bacterial count for the samples added to soybean meal compared with the witness , And there is a convergence of the general number of yeast and breakfast for the samples added to soy flour, which is within the natural area. The results also showed an increase in the profitability of the mortadella. This increase was achieved by increasing the added meal to 115.81 and 110.76% in the samples of mortadella with low fat and whole fat soya meal at 21%, respectively. تم تصنيع المرتديلا من اللحم البقري من الدرجة الثانية, بإضافة دقيق فول الصويا (كامل الدسم, منزوع الدسم) بنسب مختلفة 13,11, 15, 17, 19, 21%, تم تحديد التغير في التركيب الكيميائي (الرطوبة, البروتين, الدهن, كلور الصوديوم, الرماد, الحموضة, الـ pH, رقم البيروكسيد), وكذلك التغير في الخواص الحسية (الطعم, اللون, القوام, الرائحة, المظهر), والخواص الميكروبية (التعداد العام للبكتريا الهوائية, الخمائر والفطور, الـ E.coli, السالمونيلا), والمردودية. أظهرت نتائج التحاليل الكيميائية أن رطوبة المرتديلا تزداد بازدياد نسبة دقيق الصويا المضافة لتصبح خارج المواصفة عند نسبة الصويا 21%, وبالنسبة للرماد حيث ترتفع نسبة الرماد بارتفاع نسبة دقيق الصويا المضاف لكنها تبقى أقل من 3.2% المحددة ضمن المواصفة, كما لوحظ انخفاض في نسبة الدهن بعد إضافة دقيق الصويا (كامل الدسم, منزوع الدسم) على حد سواء لتبقى ضمن المواصفة, وبالنسبة للبروتين فان جميع العينات مع الشاهد ضمن المواصفة (12% كحد أدنى) مع ارتفاع نسبة البروتين بإضافة دقيق الصويا, وبالنسبة للملح فان نسبته ضمن جميع العينات مطابق للمواصفة (2% كحد أعلى), أما بالنسبة لقيم البيروكسيد أبدت تناقصاً بزيادة نسبة دقيق الصويا. وبينت الاختبارات الحسية أن جميع الخواص الحسية تتحسن باضافة دقيق فول الصويا في جميع الخلطات عدا الخلطة التي تصل فيها نسبة دقيق فول الصويا إلى 21%. كما بينت الاختبارات الميكروبية خلو المرتديلا من بعض الأحياء الممرضة, وخاصة السالمونيلا والـ E.coli, وبينت أيضاً أن التعداد الكلي للبكتريا الهوائية والخمائر والفطور كان ضمن حدود المواصفة القياسية السورية, ويلاحظ انخفاض في التعداد العام للبكتريا بالنسبة للعينات المضاف لها دقيق فول الصويا مقارنة مع الشاهد, كما يوجد تقارب بالتعداد العام للخمائر والفطور بالنسبة للعينات المضاف اليها دقيق الصويا وهي ضمن المجال الطبيعي. كما أظهرت النتائج زيادة في مردودية المرتديلا وهذه المردودية تزداد بزيادة الدقيق المضاف لتصل إلى 115.81, 110.76% في عينات المرتديلا المضاف لها دقيق الصويا منزوع الدسم وكامل الدسم بنسبة 21% على التوالي.